The Relationship Between Oil and Natural Gas Prices on the Malaysian Economic Sectors - Surayya Mohd Saudi, Nur; Hock Tsen, Wong; Latif Harun, Abdul; Zainal Ariffin, Zailin; Zahidah Syafii, Nur; Shakir Mohd Saudi, Ahmad; Khairul Amri Kamarudin, Mohd; Hafiz Md Saad, Muhammad; ., . (International Journal of Engineering and Technology, 2018)
This study has investigated the relationship between the changes in oil and natural gas prices on the Malaysian economic sectors. Four economic sectors were selected namely manufacturing, services, agriculture, and mining. However, there was less study conducted at the sector level. Hence, the goal of this paper is to explore the impact of oil and gas prices on economic sectors GDP. This study has conducted econometrics modelling based on the ARDL bound testing with the spanning time series data from year 1987 to 2017. The empirical findings revealed that the relationship between the oil and natural gas prices in the manufacturing and services sector is negative, while the agriculture sector showed a positive relationship, and the mining sector showed no relationship. The empirical findings concluded that the manufacturing and services sectors that consumed more energy are dependent on the price changes. Meanwhile, the agriculture sector is a highly subsidised sector which has a positive relationship with energy prices. In the policy recommendation, Malaysia has to apply the energy pricing policy by offering energy subsidy to the high energy consumed sectors. Finally, Malaysia should develop policies that can diversify its energy resources and increase the shares of renewable energy sources.Â